Staphylococcus aureus type I signal peptidase: essential or not essential, that’s the question - Hazenbos, Wouter L. (Microb Cell, 2017)
Secretion of proteins into the extracellular environment is crucial for the normal physiology and virulence of pathogenic bacteria. Type I signal peptidase (SPase I) mediates the final step of bacterial secretion, by cleaving proteins at their signal peptide once they are translocated by the Sec or twin-arginine (Tat) translocon. SPase I has long been thought to be essential for viability in multiple bacterial pathogens. Challenging this view, we and others have recently created Staphylococcus aureus bacteria lacking the SPase I SpsB that are viable and able to grow in vitro when over-expressing a native gene cassette encoding for a putative ABC transporter. This transporter apparently compensates for SpsB's essential function by mediating alternative cleavage of a subset of proteins at a site distinct from the SpsB-cleavage site, leading to SpsB-independent secretion. This alternative secretion system also drives the main mechanism of resistance to an arylomycin-derived SpsB inhibitor, by means of mutations in a putative transcriptional repressor (cro/cI) causing over-expression of the ABC transporter. These findings raise multiple interesting biological questions. Unraveling the mechanism of SpsB-independent secretion may provide an interesting twist to the paradigm of bacterial secretion.